Persistent trade-offs balance competition and colonization across centuries - Talia Backman; Jiajun Cui; Emma Caullireau; Ella Bleak; Ilja Bezrukov; Patricia Girardi; Aubrey Hawks; Jesse R. Lasky; Sergio M. Latorre; Joel M. Erberich; Lua Lopez; Manuela Neumann; et al. (Proceedings of the National Academy of Sciences, 2026)
Microbial competition drives rapid adaptation, often forcing organisms to specialize in new ecological niches. Adaptations that improve competitive ability can reduce performance in other environments creating trade-offs. Whether such trade-offs persist in nature—or are eroded as lineages adapt through compensatory changes—remains largely unknown. Here we show that a trade-off between competitive ability and host colonization has been stably maintained in natural Pseudomonas populations for centuries. Wild plant-pathogenic Pseudomonas compete using tailocins—phage-derived molecular weapons that bind to specific cell-surface receptors. Genomic surveys and functional assays reveal that the most broadly lethal tailocins remain rare—while the tailocin’s production increases competitive killing, it also compromises plant colonization. We determine that the polymorphisms behind this trade-off are not transient—historical genomes spanning two centuries show that the trade-off has been maintained for at least 10 5 to 10 6 generations. Our results demonstrate that, in natural populations, a trade-off between competition and pathogenicity is fundamental and not easily overcome.